A thin-walled structure with tailored properties for axial crushing. (July 2019) - Lin, Ye; Min, Junying; Li, Yongji; Lin, Jianping
Highlights: A design strategy of thin-walled structures with tailored properties is proposed. An analytical model is obtained for the crashworthiness with tailored properties. The effect of tailored property on the crushing of thin-walled structures is studied. Abstract: This study proposed a design strategy of a thin-walled structure with tailored properties for axial crushing. The thin-walled structure was divided into multiple sections and the material properties in each section differ from those in the neighboring sections. The crashworthiness of this structure was affected by distributions and material strengths of sections. Analytical model and finite element model were used to provide predictions of mean and peak crushing forces of the thin-walled structure with tailored properties during axial crushing. An optimal design strategy, in which sections with higher strength are distributed at ridgelines along the longitudinal direction, is recommended not only to increase the mean crushing force but also to acquire acceptable peak crushing force.